BINTU SYATI’ DAN PENAFSIRANNYA TERHADAP SURAH AL-‘ASR DALAM KITAB AT-TAFSIR AL-BAYANI LIL QUR’ANIL KARIM - Wali Ramadhani (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2018)
This article discusses about the biography of Bintu Syati’ and her bayani interpretation. Her Interpretation work titled at-Tafsir al-Bayani lil Quranil Karim is the best representation of the methodology of the Quran interpretation with a literary nuance initiated by her own husband, Amin al-Khuli. The author, in this article, also describes the application of Bayani interpretation method in QS al-‘As}r.